Urgency of Legal Protection for Religious Scholars in Articles on Blasphemy from the Perspectives of Criminology and Victimology - Fithry, Abshoril; Sjaifurrachman, Sjaifurrachman (Journal of Progressive Law and Legal Studies, 2024)
The urgency lies in the ambiguous definition, which allows this article to be interpreted in various ways and potentially forces anyone into the realm of criminal law. This is found in Article 156a, which states that anyone who deliberately expresses sentiments or performs acts essentially hostile, abusive, or blasphemous against a religion practiced in Indonesia shall be punished with imprisonment for a maximum of 5 years in public. The phrase "in public" is the subject of debate and could render the article ambiguous, allowing it to be used to target anyone desired to fulfill the criteria. The purpose of this research is to prevent the continued use of this ambiguous article for personal or group interests, and to stop the criminalization of speakers using this provision.